Evaluation of peanut skin and grape seed extracts to inhibit growth of foodborne pathogens. Issue 6 (31st August 2017) - Levy, Jason; Boyer, Renee R.; Neilson, Andrew P.; O'Keefe, Sean F.; Chu, Hyun Sik S.; Williams, Robert C.; Dorenkott, Melanie R.; Goodrich, Katheryn M.
Abstract: Peanut skin extract (PSE) and grape seed extract (GSE) are derived from waste products in the wine and peanut industries, respectively. Both have high concentrations of polyphenols, known to possess antioxidant and antimicrobial properties. PSE primarily contains "A‐type" procyanidins, while GSE primarily contains "B‐type" procyanidins. These differ structurally, but are both isomers of epicatechin dimers. The objective of this study was to evaluate the antimicrobial effects of PSE containing A‐type procyanidins and GSE containing B‐type procyanidins against select foodborne pathogens ( Listeria monocytogenes, Escherichia coli O157:H7, and Salmonella Typhimurium). The minimum inhibitory concentration (MIC) of the two extracts on L. monocytogenes, E. coli O157:H7, and S.  Typhimurium was determined using the pour plate method. GSE had a significantly lower MIC ( p  ≤ .05) than PSE for L. monocytogenes (GSE = 60.6 ppm, PSE > 68.2 ppm) and S.  Typhimurium (GSE = 45.7 ppm, PSE = 60.6 ppm), but no difference in inhibition of E. coli O157:H7. Since GSE contributed to greater inhibition, GSE extract was fractionated into monomer‐rich (consisting primarily of catechins, epicatechins, and epicatechin gallates) and oligomer‐rich (consisting of dimers, trimers, tetramers, up to decamers) components. Growth curves of all three pathogens in the presence of full extract, monomer and oligomer fractions were compared separately. None of the extracts inhibited S.  Typhimurium growth. Generally, the extract containing greater oligomer components inhibited growth of L. monocytogenes and E. coli O157:H7 when compared to the control. Results indicate that an extract with type B procyanidins higher in oligomers may have greater antimicrobial properties. Abstract : The objective of this study was to evaluate the antimicrobial effects of peanut skin extract (PSE) containing A‐type procyanidins and grape seed extract (GSE) containing B‐type procyanidins against select foodborne pathogens ( Listeria monocytogenes, Escherichia coli O157:H7, and Salmonella Typhimurium). GSE had a significantly lower MIC ( p  ≤ .05) than PSE for L. monocytogenes (GSE = 60.6 ppm, PSE > 68.2 ppm), and S . Typhimurium (GSE = 45.7 ppm, PSE = 60.6 ppm), but no difference in inhibition of E. coli O157:H7. Since GSE contributed to greater inhibition, GSE extract was fractionated.